GAYA KEPEMIMPINAN TRANSAKSIONAL, TRANSFORMASIONAL DAN KINERJA GURU - Ulil Multazam (el Hakim Press, 2023)
Creating a leadership style that is able to bring its members to improve performance in order to achieve organizational goals is not an easy thing. This is because basically humans have different behavioral characteristics according to the level of their needs. If there is a difference or gap between members' perceptions and leaders' perceptions of the perceived and expected climate, then this will allow the creation of job dissatisfaction from members, so that it can lead to abuse of rights and obligations which ultimately results in organizational goals cannot be met optimally. The school is an organization designed to have an influence on improving the quality of life of the community. Efforts to improve the quality of schools need to be organized, regulated, managed so that the quality of school performance is able to produce graduates who are able to compete in the community. The school management referred to above is related to the leadership style of the principal who is able to realize teacher performance in an effort to improve the quality of educational effectiveness. Principal is one of the most important components of education in improving teacher performance. For this reason, several studies on transactional and transformational leadership styles in the context of schools need to be understood and implemented in order to ensure the achievement of school goals with performing teachers. The purpose of writing this journal is to describe transactional leadership style, transformational leadership style and teacher performance. This study is important to discuss considering that teacher performance is largely determined by the figure of the principal. This paper is a type of library research or also called a literature study, because the author collects library data, reads, records and processes from various sources, the main data sources are from books, research results and journals. This paper is expected to provide benefits for observers who are interested in studying leadership styles and performance, especially those related to activities in schools.